The impact of quarantine due to COVID-19 pandemic on the tourism industry in Lviv (Ukraine) - Mykhailo Rutynskyi; Halyna Kushniruk (Problems and Perspectives in Management, 2020)
The global crisis caused by COVID-19 pandemic and the introduction of long-term international quarantine measures have had a very negative impact on the tourism industry. The paper aims to analyze the sectoral losses of the tourism industry during quarantine due to the COVID-19 pandemic in Lviv, a city whose historical center is included in the UNESCO World Heritage Site. The article highlights the potential of the tourism industry before the introduction of quarantine measures, as well as using extrapolation methods estimates the economic losses of the tourist industry of Lviv in the conditions of long-term quarantine. Besides, the anti-crisis measures of the city authorities to minimize the impact of quarantine due to COVID-19 pandemic on the tourism industry of Lviv are described. Based on a statistical analysis of the forecasted economic losses, it is recommended that city authorities abolish some local taxes and fees in the tourism sector to restore its potential as soon as possible.